2017
DOI: 10.5430/jnep.v7n5p120
|View full text |Cite
|
Sign up to set email alerts
|

Immersive learning in nursing education: Results of a study

Abstract: Objective: This study evaluated the effectiveness of an immersive teaching and learning approach for undergraduate nurses. Traditional classroom tutorials were combined with self-directed learning using LabTutor TM , an online learning platform, and clinical nursing simulation using high fidelity manikins. Learning modules were designed to link the student's knowledge and understanding of biosceince with clinical assessment and nursing management in order to develop clinical decision-making skills. It was anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Furthermore, recent studies revealed that students' success in doing an internship could be seen if proper and regular feedbacking had been conducted to monitor students' development and progress (Wright, Miller, Dawes, & Wrigley, 2018;Eyler & Giles, 2014;Knouse & Fontenot, 2008). Furthermore, studies also show that feedback improves student's confidence, self-awareness and enthusiasm, which will prepare them in the real-work setting (Ditzel, Hogarth, & Lesa, 2017;Rothman, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies revealed that students' success in doing an internship could be seen if proper and regular feedbacking had been conducted to monitor students' development and progress (Wright, Miller, Dawes, & Wrigley, 2018;Eyler & Giles, 2014;Knouse & Fontenot, 2008). Furthermore, studies also show that feedback improves student's confidence, self-awareness and enthusiasm, which will prepare them in the real-work setting (Ditzel, Hogarth, & Lesa, 2017;Rothman, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Immersive teaching is to immerse students in the target language environment in language teaching [5][6][7][8]. The term "immersive" in this article refers to immersing students in specific projects.…”
Section: B Immersive Teachingmentioning
confidence: 99%
“…Immersive teaching [1][2][3][4] originated in Canada in the 1960s, is a beneficial attempt of Canadian French teaching and has been proved that it is a kind of very effective teaching mode for non native language. Therefore, this teaching mode has been paid more and more attention, and has been widely applied in Canada and the United States with great success.…”
Section: Related Workmentioning
confidence: 99%